Unveiling the functional significance of the 14.3.3 protein: A key player in Paracoccidioides brasiliensis biofilm formation - Sardi, Janaina de Cássia Orlandi [UNESP]; Derissi Braz Carlton, Jaqueline [UNESP]; Marcos, Caroline Maria [UNESP]; Fusco Almeida, Ana Marisa [UNESP]; Mendes Giannini, Maria José Soares [UNESP] (Elsevier, 2024)
Paracoccidioidomycosis (PCM) is a systemic mycosis caused by Paracoccidioides spp. The interaction mediated by the presence of adhesins on the fungal surface and receptors in the extracellular matrix of the host, as well as the biofilm formation, is essential in its pathogenesis. Adhesins such as gp43, enolase, GAPDH (glyceraldehyde-3-phosphate dehydrogenase), and 14-3-3 have been demonstrated in the Paracoccidioides brasiliensis (Pb18) strain and recognized as necessary in the fungus-host interaction. The Pb 18 strain silenced to 14-3-3 showed changes in morphology, virulence, and adhesion capacity. The study aimed to evaluate the role of adhesin 14-3-3 in P. brasiliensis biofilm formation and the differential expression of genes related to adhesins, comparing planktonic and biofilm forms. The presence of biofilm was also verified in sutures in vitro and in vivo. The silenced strain (Pb14-3-3 aRNA) was compared with the wild type Pb18, determining the differential metabolic activity between the strains by the XTT reduction assay; the biomass by violet crystal and the polysaccharides by safranin, even as morphological differences by microscopic techniques. Differential gene expression for adhesins was also analyzed, comparing the relative expression of these in planktonic and biofilm forms at different times. The results suggested that the silencing of 14-3-3 protein altered the ability to form biofilm and its metabolism. The quantity of biomass was similar in both strains; however, the formation of exopolymeric substances and polysaccharide material was lower in the silenced strain. Our results showed increased expression of enolase, GAPDH, and 14-3-3 genes in the first periods of biofilm formation in the Pb18 strain. In contrast, the silenced strain showed a lower expression of these genes, indicating that gene silencing can influence the expression of other genes and be involved in the biofilm formation of P. brasiliensis. In vitro and in vivo assays using sutures confirmed this yeast's ability to form biofilm and may be implicated in the pathogenesis of paracoccidioidomycosis.
Keywords: 14-3-3 protein; adhesins; Biofilm; Paracoccidioides brasiliensis; Virulence